Point‐of‐Care Screening, Prevalence, and Risk Factors for Hepatitis B Infection Among 3, 728 Mainly Undocumented Migrants From Non‐EU Countries in Northern Italy. Issue 2 (26th November 2014) - El‐Hamad, Issa; Pezzoli, Maria Chiara; Chiari, Erika; Scarcella, Carmelo; Vassallo, Francesco; Puoti, Massimo; Ciccaglione, Anna; Ciccozzi, Massimo; Scalzini, Alfredo; Castelli, Francesco; ,
Abstract : Background: Screening migrants from areas where hepatitis B virus (HBV) infection is endemic is important to implement preventive measures in Europe. The aim of our study was to assess (1) the feasibility of point‐of‐care screening in a primary care clinic and (2) hepatitis B surface antigen (HBsAg) prevalence, associated risk factors, and its clinical and epidemiological implications in undocumented migrants in Brescia, northern Italy. Methods: A longitudinal prospective study was conducted from January 2006 to April 2010 to assess HBsAg reactivity and associated risk factors among consenting undocumented migrants who accessed the Service of International Medicine of Brescia's Local Health Authority. Genotyping assay was also performed in HBV DNA‐positive patients. Results: Screening was accepted by 3, 728/4, 078 (91.4%) subjects consecutively observed during the study period, 224 (6%) of whom were found to be HBsAg‐positive. HBsAg reactivity was independently associated with the prevalence of HBsAg carriers in the geographical area of provenance ( p < 0.001). On the contrary, current or past sexual risk behaviors (despite being common in our sample) were not associated with HBV infection. Half of the HBsAg patients (111/224) had either hepatitis B e‐antigen (HBeAg)‐positive or ‐negative chronic HBV infection with a possible indication for treatment. HBV genotypes were identified in 45 of 167 HBV‐infected patients as follows: genotype D, 27 subjects; genotype A, 8; genotype B, 5; and genotype C, 5. The geographical distribution of genotypes reflected the geographic provenance. Conclusions: Our results suggest that point‐of‐care screening is feasible in undocumented migrants and should be targeted according to provenance. Case detection of HBV infection among migrants could potentially reduce HBV incidence in migrants' contacts and in the general population by prompting vaccination of susceptible individuals and care of eligible infected patients.